PROGRAM COACHING DALAM MENINGKATKAN SUPERVISI AKADEMIK - Nafisati, Novi; Widodo, Hendro; Suyatno, Suyatno (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to determine the effectiveness of a coaching program in improving the academic supervision competency of leading teachers. This study used a qualitative approach with a case study method, data were collected through semi-structured interviews and focus group discussions. The results indicate that a coaching program can be a solution to improve the quality of education by enhancing teacher competency. The primary motivation for coaching is to help teachers find solutions to challenges and share ideas, which are key drivers of the program's success. The coaching material covers various approaches and important principles. Participants highlighted coaching that helps with aspects of mindfulness, understanding the observed lesson preparation process, and key elements such as partnership, two-way communication, full attendance, insightful questions, active listening, sensitivity to conditions, and avoiding assumptions. Furthermore, the use of the TIRTA flow in each session was also considered essential. The success of coaching is greatly influenced by the collaboration of the principal, colleagues, and fellow leading teachers. The success of coaching is greatly influenced by the collaboration of the principal, colleagues, and fellow leading teachers. The coaching program faced several significant obstacles. The main obstacles included a lack of support and collaboration from colleagues. Furthermore, time constraints in program implementation and a less than conducive environment were also problems.